‘A Natural and Voluntary Dependence’: The Royal Academy of San Carlos and the Cultural Politics of Art Education in Mexico City, 1786–1797. - DEANS‐SMITH, SUSAN (Bulletin of Latin American Research, 2010)
In this article, I explore the controversies that characterised the foundational years of the Royal Academy of San Carlos of Painting, Sculpture, and Architecture in Mexico City (1786–1797). They provide provocative insights into questions of competing agendas and ambitions among the artists and bureaucrats of the royal academy. They also illuminate contemporary understandings about the hierarchical relationships between a metropolitan power, Spain, and its American colonies and their visual culture and artistic production, which mirror broader political hierarchies and relationships of power and subordination.